[Mga Kababayan ; Tuloy ang ikot ng mundo ; Japayuki ; Kaunlaran ; New York, New York ; Lahat may pag-asa [videorecording] - producer, executive; Lazaro, Cheche (Quezon City Probe Productions, 1991)
Francis Magalona talks about his singing career and the effect of his song on the youth. APO sings about personal tragedies. Marites Temple, a Japayuki composed and sings the song about overseas workers, the Gulf War and the Maricris Sioson. Joey Ayala and Bagong Lumad talk about the destruction of the environment. Gary Granada sings about freedom and happiness. Talks also about Imelda Marcos' homecoming and the people's reaction to her. The Side A Band sings about hope in every disaster.
Mga Kababayan (7 min.) -- Tuloy ang ikot ng mundo (10 min.) -- Japayuki (9 min.) -- Karaniwang tao (9 min.) -- Kaunlaran (9 min.) -- New York, New York (6 min.) -- Lahat may pag-asa (15 min.)
VHS.
Keywords: Magalona, Francis -- Interviews; Temple, Marites -- Interviews; Ayala, Joey -- Interviews; Apo Hiking Society; Side A Band; Singers -- Philippines -- Interviews